TAR-independent transactivation of the murine cytomegalovirus major immediate-early promoter by the Tat protein. - Kim, Y S (1993)
Tat is a transactivator of human immunodeficiency virus type 1 (HIV-1) that stimulates gene expression via an RNA target sequence (TAR) by augmenting transcriptional initiation and/or elongation from the HIV-1 long terminal repeat promoter. Here we show that Tat is able to transactivate the murine cytomegalovirus (MCMV) major immediate-early promoter (MIEP), which lacks sequence similarity with the HIV-1 long terminal repeat TAR element. Surprisingly, deletion of the upstream enhancer region (-610 to -146) of the MCMV MIEP abrogated Tat responsiveness. This result suggests that Tat requires a DNA target for function. Quantitation of RNA and protein indicates that Tat stimulates expression from the MCMV MIEP at both the transcriptional and translational levels. Deletion analysis of the MIEP indicates that there is likely to be interplay between the enhancer region, a sequence upstream of the known enhancer which negatively affects expression, and the Tat protein.